Analisis Kualitas Penerjemahan Pada Novel Gadis Jakarta Karya Najib Kailani - Amanda Putri (Kementerian Sekretariat Negara Republik Indonesia, 2026)
This study examines the translation quality of the novel Gadis Jakarta by Najib Kailani from Arabic into Indonesian. Translation quality is an essential aspect to ensure that meaning is accurately conveyed and acceptable to target readers. This study aims to analyze the translation quality based on Nababan’s model, which includes accuracy, acceptability, and readability. This research employs a descriptive qualitative method with a quantitative approach to scoring. The data consist of 140 translation units taken from chapters 3 and 5 of the novel. The data were assessed by three respondents using a three-point scale for each aspect. The results show that the overall translation quality is categorized as high, with average scores indicating that readability is the highest aspect, followed by acceptability and accuracy. This indicates that the translation is generally easy to understand and acceptable in the target language, although minor inaccuracies in meaning transfer are still found in some data. In conclusion, the translation of Gadis Jakarta demonstrates good quality in conveying meaning from the source language into the target language, with a need for improvement in maintaining semantic accuracy.